Chiral Edge Current in Nematic Cell Monolayers - V. Yashunsky; D. J. G. Pearce; C. Blanch-Mercader; F. Ascione; P. Silberzan; L. Giomi (Physical Review X, 2022)
Collectively migrating cells in living organisms are often guided by their local environment, including physical barriers and internal interfaces. Well-controlled in vitro experiments have shown that, when confined in adhesive stripes, monolayers of moderately active spindle-shaped cells self-organize at well-defined angle to the stripes’ longitudinal direction and spontaneously give rise to a simple shear flow, where the average cellular orientation smoothly varies across the system. However, the impact of physical boundaries on highly active, chaotic, multicellular systems is currently unknown, despite its potential relevance. In this work, we show that human fibrosarcoma cells (HT1080) close to an interface exhibit a spontaneous edge current with broken left-right symmetry, while in the bulk the cell flow remains chaotic. These localized edge currents result from an interplay between nematic order, microscopic chirality, and topological defects. Using a combination of in vitro experiments, numerical simulations, and theoretical work, we demonstrate the presence of a self-organized layer of +1/2 defects anchored at the boundary and oriented at a well-defined angle close to, but smaller than, 90° with respect to the boundary direction. These self-organized defects act as local sources of chiral active stress generating the directed edge flows. Our work therefore highlights the impact of topology on the emergence of collective cell flows at boundaries. It also demonstrates the role of chirality in the emergence of edge flows. Since chirality and boundaries are common properties of multicellular systems, this work suggests a new possible mechanism for collective cellular flows.